Lipidome Profiling of APOE4 AD brains implicated unresolved neuroinflammation involving polyunsaturated fatty acid metabolism. (20th December 2022) - Asante, Isaac; Ebright, Brandon; Wang, Shaowei; Poblete, Roy; Arvanitakis, Zoe; Bennett, David A; Louie, Stan G; Yassine, Hussein N.
Abstract: Background: The Apolipoprotein E4 (APOE4) allele has been associated with an accentuated response to brain inflammation and increases the risk of AD dementia progression. Among inflammation signaling pathways, eicosanoids play a prominent role in neurodegeneration. Method: This study compared measures of the eicosanoid lipidome from patients with AD dementia compared to age and sex‐matched controls with no cognitive impairment (NCI), stratified by APOE genotypes using postmortem brain tissues from the Religious Order Study (n = 42). Result: Targeted lipidomic analysis by mass spectrometry of the dorsolateral prefrontal cortex demonstrated lower levels of omega‐3 fatty acids eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA), and DHA‐derived neuroprotectin D1 (NPD‐1) in persons with lower global cognitive function, independent of age, sex and education years. APOE4 was associated with greater pro‐inflammatory lipids (e.g., PGD2, PGE2, 12‐HHT, LTB4 and 5‐HETE) and pro‐resolving lipids (eg. lipoxins, resolvins and EETs) in patients with dementia (Figure 1). Pathway analysis implicates greater activation of calcium dependent phospholipase A2 (cPLA2), 5‐lipoxygenase (5‐LOX) and soluble epoxide hydrolase (sEH) underlying the observed lipidomic profile. Conclusion: These results confirm a chronic state of unresolved inflammation in the AD dementia brain that is accentuated in carriers of the APOE4 allele and identify novel therapeutic targets.